An epidemiological study of the association between risk factors and skin cancer incomplete excisions - João Vitor Pithon Napoli; Gabriela Ducioni Matos (Revista Brasileira de Cirurgia Plástica)
Introduction: The increasing incidence of skin cancer leads to a high number of surgical procedures worldwide. The surgical treatment of skin cancer's main objective is its complete excision, preserving the function and the best aesthetic result. Incomplete initial resection can result in recurrences and major damage. The objective is to analyze the risk factors for positive margins in the follow-up of cutaneous lesions surgically removed, for one year, in the plastic surgery department of the Royal Perth Hospital. Methods: A survey of histopathological samples from 947 operated patients was analyzed. All patients with confirmed incomplete excision (IE) underwent a second surgery or even a third time. Results: In total, 947 lesions were found, 6.6% of surgeries had compromised margins, with a histopathological distribution of 75% of basal cell carcinoma, 21.4% of squamous cell carcinoma, and 3.6% of other lesions. The relation of the presence of compromised surgical margins between the SCC, compared to BCC, leads to a relative risk of 2.8 and a p-value of 0.041, which suggests that the SCC is a risk factor for the presence of compromised surgical margins. For staging, the need for a second surgical approach was present in 61.29% of the patients, 20.9% were under observation, 3.2% were absent from the service, 8% went directly to chemotherapy or radiotherapy, and 6.4% rescheduled the surgery. Conclusion: Knowledge of risk factors for positive margins is necessary for the surgeon to understand the prognosis and monitoring of each patient.